Simultaneous Kinetic-Potentiometric Determination of Aluminum(III) and Iron(II) - KARIMI, M.A.; MAZLOUM ARDAKANI, M.; ZAREA ZADEH, N. (Asian Journal of Chemistry, 2010)
The H-point standard addition method (HPSAM), partial least squares (PLS) and principal component regression (PCR) are suggested in this study for simple and accurate simultaneous determination of Fe(II) and Al(III). In this work, the oxidation reaction of Fe(II) to Fe(III) in the presence of peracetic acid (PAA) as oxidant is based of the method. The complexing reaction of Fe(III) and Al(III) with fluoride ion has a difference rate at certain reaction conditions. So the exist of oxidant is necessary for oxidation of Fe(II) to Fe(III) that has no effect on Al(III) ion. The rate of consume fluoride ion for making complex is detected with a fluoride ion selective electrode (FISE). The results show that simultaneous determination of Fe(II) and Al(III) can be done in their concentration ranges of 0.5-40.0 and 1.0-25.0 μg mL-1, respectively. The total relative standard error for applying the PLS and PCR methods on 8 synthetic samples was 3.43 and 3.85, respectively in the concentration ranges of 3.0-25.0 μg mL-1 of Fe(II) and 3.0-15.0 μg mL-1 of Al(III). The proposed methods (HPSAM, PLS and PCR) were applied to the simultaneous determination of Fe(II) and Al(III) in different water samples.